The Legal Framework Of The Declaration Of State Of Emergency And Martial Law In The Jordanian Constitution (Journal of Namibian Studies : History Politics Culture, 2023)
The aim of this research is to examine and analyze the legal system for declaring the state of emergency in the Jordanian constitution of 1952 and its amendments. In this research you can find a description of what State of Emergency is, its characteristics based on the Jordanian constitution, and the laws that govern declaring  the state of emergency, types of the state of emergency, ways of declaring emergency and structural flaws and loopholes in the laws that govern the state of emergency in the constitution., This research illustrates the impact of declaring the state of emergency on civilian's citizens and non-citizens. Conclusions and recommendations for modifications  of the laws of the state of emergency are also included by the authors to protect the civil and political rights of citizens.